Database processing : - Kroenke, David M. (Pearson Prentice Hall, 2006)
Database Processing assures that you will learn marketable skills. By presenting SQL SELECT statements near the beginning of the book readers will know early on how to query data and obtain results–seeing firsthand some of the ways that database technology is useful in the marketplace. By utilizing free software downloads, you will be able to actively use a DBMS product by the end of the 2nd chapter. Each topic appears in the context of accomplishing practical tasks. Its spiral approach to database design (incorporating all 3 sources: from the integration of existing data, from new information, and the need to redesign an existing database) provides users with enhanced information not available in other database books on the market. Topics include: SQL, database design, implementation, processing, access standards, and business intelligence. An excellent reference and handbook for information systems professionals such as database administrators, database designers, systems analysts, web-database developers, and programmers of database applications.